Design and simulation of a collision notification application with geocast routing for car-to-car communications (2015)
Introduction: Car-to-X Communications are envisioned to improve road safety, traffic efficiency, and information services through short-range and real-time systems. The enabling applications have varied requirements such as low latency, specific forwarding patterns, and reliable data exchange between vehicles and infrastructure. Hence, a cross-layer architecture for vehicular applications should be defined according to the goals of the implementation, so as to consider proper routing and dissemination mechanisms, communication protocols, and the application’s design and operation. Methods: In this context, we propose the characterization of the upper layers of a safety-oriented Car-to-Car application.